Characterization of the Monkeypox Virus [MPX]-Specific Immune Response in MPX-Cured Individuals Using Whole Blood to Monitor Memory Response - Elisa Petruccioli; Settimia Sbarra; Serena Vita; Andrea Salmi; Gilda Cuzzi; Patrizia De Marco; Giulia Matusali; Assunta Navarra; Luca Pierelli; Alba Grifoni; Alessandro Sette; Fabrizio Maggi; et al. (Vaccines)
Background: Monkeypox (Mpox) is a zoonotic disease caused by monkeypox virus (MPXV), an Orthopoxvirus (OPXV). Since we are observing the first MPXV outbreak outside the African continent, the general population probably does not have a pre-existing memory response for MPXV but may have immunity against the previous smallpox vaccine based on a live replicating Vaccinia strain (VACV). Using a whole blood platform, we aim to study the MPXV- T-cell-specific response in Mpox-cured subjects. Methods: We enrolled 16 subjects diagnosed with Mpox in the previous 3–7 months and 15 healthy donors (HD) with no recent vaccination history. Whole blood was stimulated overnight with MPXV and VACV peptides to elicit CD4 and CD8 T-cell-specific responses, which were evaluated by ELISA and multiplex assay. Results: Mpox-cured subjects showed a significant IFN-γ T-cell response to MPXV and VACV. Besides IFN-γ, IL-6, IP-10, IL-8, IL-2, G-CSF, MCP-1, MIP1-α, MIP-1β, IL-1Rα, and IL-5 were significantly induced after specific stimulation compared to the unstimulated control. The specific response was mainly induced by the CD4 peptides MPX-CD4-E and VACV-CD4. Conclusions: We showed that MPXV-specific responses have a mixed Th1- and Th2-response in a whole blood platform assay, which may be useful for monitoring the specific immunity induced by vaccination or infection.